Buy Now Pay Later Transactions (BNPL) in Indonesia: Implications for Maqāṣid Sharia in the Digital Era - Firdaus, Beni; Fauzan, Fauzan; Yenti, Endri; Yufriadi, Ferdi; Rahmiati, Rahmiati; A Afifi, Abdullah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Buy Now Pay Later (BNPL) services have gained significant popularity among Indonesian customers, particularly within the younger demographic that values convenience and flexibility in online shopping. This research uses a qualitative approach to examine the applications of Islamic law on the utilization of BNPL inside digital transactions in Indonesia, while also assessing its effects on consumer behavior and economic stability. The findings indicate that although Buy Now Pay Later (BNPL) provides ease and accessibility for consumers, substantial obstacles exist in aligning this practice with maqāṣid sharia principles, especially with usury and consumer protection issues. Factors such as financial literacy, governmental laws, and product transparency significantly impact the adoption of BNPL, shaping customer comprehension and utilization of these services. Islamic financial institutions bear a significant obligation to deliver several itemsthat not only meet the demands of consumers but also sharia compliance. As such, this research contributes to strengthening the integration between digital technology and the financial system, as well as supporting sustainable economic growth that is compliant with Shariah principles.